Natural hydrogen continuous emission from sedimentary basins: The example of a Brazilian H2-emitting structure. (1st March 2019) - Prinzhofer, Alain; Moretti, Isabelle; Françolin, Joao; Pacheco, Cleuton; D'Agostino, Angélique; Werly, Julien; Rupin, Fabian
Abstract: Hydrogen escaping from sedimentary basins has already been described in various parts of the world. Some of these leakages have been identified by superficial circular depressions, also called "fairy circles". Gas detection measurements, randomly repeated after a few months have shown that the amount of hydrogen present in soils is not constant neither versus time nor versus position in a given structure. Permanent monitoring gas analyzers were installed in the ground to estimate hydrogen flow outgassing from a topographical circular depression located in Brazil. Data show that a hydrogen flux occurs during the hottest moment of the day, as shown with permanent sensors set at a regular spacing. The process may look like a soil evaporation. In that same structure, other detectors show much higher and irregular gas output which present an unclear correlation as a function of ambient temperature and atmospheric pressure. The relationship with temperature suggests a role of water saturation driving the overall hydrogen fluxes. The reported geochemical data imply that (1) one measurement taken at a given hour on a structure cannot be considered as quantitative, as it varies too much with time and is also probably related to the soil perturbation induced by the shallow drilling, (2) hydrogen released through the soils of the studied structure is recharged daily, (3) hydrogen flux is high enough to reach the surface without being buffered by water or bacterial activity within the soil and (4) soil cannot be solely considered as a hydrogen sink but also, at least in some areas, as a hydrogen emitter. This appears to highlight that the subsurface may be considered in this site as a source of natural hydrogen, clearly differentiated from a biochemical system of atmospheric H2 consumed by bacteria. Highlights: Hydrogen monitoring of a continental circular structure in sediments. Periodicity of hydrogen seeping out of the soils. Soil in the studied area is a hydrogen emitter and not a hydrogen sink. Daily periodicity of hydrogen leakage out of the ground. Tentative estimate of hydrogen flux in a continental area.